Role of Laminin in Oral Carcinogenesis - Preeti, Ahankare; Gokul, Sridharan; Sangeeta, Patankar (The Journal of Dentists, 2019)
Oral carcinogenesis is characterized by significant alterations occurring at the phenotypic and genotypic level resulting in uncontrolled proliferation and evasion of apoptosis. With growing tumor mass, a switch of metabolism and angiogenesis becomes important for the further development of the disease. Invasion and subsequent metastasis of the malignant cells are basic requirement for tumor promotion and progression. Cell migration plays an important in embryogenesis, inflammatory immune response, wound healing and cancer invasion. One of the important factors responsible for the tumor progression is the alteration seen in extracellular matrix proteins. Extracellular matrix (ECM) includes a group of structural proteins, glycoproteins, and proteoglycans that function as a physical scaffold to maintain tissue structure and provides biochemical signals to modulate cellular function. Basement membranes are thin layers of ECM that form the supporting structure under epithelial and endothelial cells. The protein composition of basement membrane is mainly inclusive of type IV collagen, laminins, entactins, and proteoglycans. Laminin is biologically active part of the basement membrane and influences cell differentiation, migration and cell adhesion. They are an important and biologically active component of the basal lamina, influencing cell differentiation, migration, and adhesion. Laminin reflects the integrity of basement membrane better than the other extracellular matrix (ECM) proteins and thus, may be used as a marker suggestive of the basement membrane status during tumorigenesis. Oral squamous cell carcinoma is an important epithelial malignancy and altered laminin expression in OSCC is an important process in its invasion and metastasis. An understanding of the role of laminin in OSCC may aid in its utility as a biomarker to determine the prognosis and treatment planning of OSCC.